Epigenetic hotspots in cancer - Pestana, Daniel José Formica (2021)
DNA methylation is one of the most studied epigenetic events. In normal cells, it assures the regulation of gene expression without changing the genetic code. However, alterations in DNA methylation are now widely recognized as a contributing factor in tumorigenesis. The bulk of research done in cancer epigenetics focuses on one of two events: promoter hypermethylation and global hypomethylation. Advances in the understanding of how DNA methylation shapes the chromatin’s organization and how the later affects gene expression have been made. Less is known about how DNA methylation affects genes not only locally but also at a distance. We hypothesized that during tumorigenesis specific genomic regions are more susceptible to DNA methylation (epi-hotspots) and other are resistance to DNA methylation changes (epi-blackholes). We also hypothesized that these regions might persist in tumor cells by exerting some selective pressure in the primary tumor clones. By performing a pan-cancer analysis comparing normal to stage-I primary stage-I primary tumor samples gathered from TCGA consortium, we observed that both epi-hotspots and epi-blackholes occurred in all of the analyzed cancer cohorts. Furthermore, generally, epi-hotspots were able to predict gene expression alterations during tumorigenesis, and epi-blackholes were predictors of maintenance of gene expression during tumor initiation, which was in accordance with our hypothesis. We also found that several epi-hotspots and epi-blackholes are predictors of survival in stage-III tumor patients, which may provide potential study targets for candidate prognostic biomarkers. In summary, this study provides new evidence that regional methylation patterns potentially might exert selective pressure in tumor initiation by influencing genome-wide gene expression, and that these traits might be used to develop novel diagnostic and prognostic candidate biomarkers.